[12] Challenges in hypospadias surgery - Ahmed Masaoud Mohamed (Taylor & Francis Group, 2018)
Objective: To provide a summary of the possible challenges we may face in managing patients with hypospadias from birth to adulthood, as the treatment of hypospadias is full of challenges not because of the operation technique itself but because of other factors such as delayed diagnosis, continuation of regular long-term follow-up, and relatively high rate of complications. Methods: Collection of personal experience and literature regarding hypospadias management and its challenges with some suggestions of how to deal with these challenges in better ways. Many known surgical procedures have been established for hypospadias. The selection of the right procedure for each patient is an individual decision that varies with the location of the urethral orifice, other associated problems, and the centres experience, and this decision is usually taken intraoperatively. The management of these patients should also include the psychosocial aspect and the continued education of the patient and family. Results: It is valuable that every surgeon dealing with hypospadias is aware of these challenges and how to manage them. The management of other aspects like psychosocial support should be considered. Conclusion: A comprehensive knowledge of these challenges and their management is necessary for every surgeon dealing with such patients. Management of hypospadias is not only the surgical procedure, but it includes at the same time the long-term follow-up, psychosocial support, and continuous patient and family education.